نموذج مقترح لقياس وتوزيع الدخل في شركات الأشخاص - زيود, لطيف (Latakia University Journal - Economic and Legal Sciences Series, 2019)
إن قياس الدخل في شركات الأشخاص يتم بشكل يتفق مع قياسه في المنشآت الأخرى سواء أكانت فردية أو شركات أموال أو شركات عامة على اعتبار أن قياس الدخل يعتمد على المبادئ المحاسبية المقبولة عموما مع بعض الاختلافات البسيطة الناتجة عن الفروقات في الشكل القانوني للمنشآة, إلا أنه يختلف بصورة جوهرية عن توصيات المجامع المهنية للمحاسبة خصوصا فيما يتعلق بالمعالجة المحاسبية لفوائد القروض الشخصية للشركاء أو قروض الغير. من جهة أخرى يتم توزيع الدخل في شركات التضامن بما ينسجم مع بنود عقد الشراكة بين الشركاء وبما لا يتناسب مع تطور الفكر المحاسبي وتوصيات المجامع المهنية للمحاسبة مما يضعف إمكانية المقارنة بين المنشآت المتماثلة أو غير المتماثلة ويضعف إمكانية حساب النسب المحاسبية بصورة دقيقة وموحدة لذلك جاءت محاولة الباحث في قياس وتوزيع الدخل لشركات الأشخاص بما يتناسب مع المبادئ المحاسبية المقبولة عموما وبما يتناسب مع تطور الفكر المحاسبي بهدف تطوير هذه المعالجة وتوحيد إجراءات قياس وتوزيع الدخل بعيدا عن الشكل القانوني للوحدة الاقتصادية. The measuring of income in the partnership companies accords with the measuring in other establishments be it private, public, or financial companies depending on the fact that measuring of income depends on the generally accepted accounting principles with some slight differences that result from the legal from differences in the establishments but they substantially differ from the recommendations of the professional accounting associations concerning the accounting processes of the personal loan interests of companies or the loans of others. On the other hand, the distribution of the income in the partnership companies take place in accordance with the terms of the contract signed by the partners and in away that does not accord with the development of the accounting mentality and the recommendations of the professional accounting associations the thing that weakens the possibility of comparing the similar and different establishments. It also weakens the possibility of measuring the accounting proportions in an accurate and unified way. The thing that led to the attempt, on the side of the researcher, to measure and distribute the income in the partnership companies in accordance with the generally accepted accounting principles and in accordance with the development the accounting mentality, the thing that aims at developing this process and unifying the measuring procedures and distributing the income away from the legal from of the economical unity.